Challenges and advances in glioblastoma targeted therapy: the promise of drug repurposing and biomarker exploration - Bae, William Han; Maraka, Stefania; Daher, Ahmad (Frontiers in Oncology, 2024)
Glioblastoma remains the most prevalent and aggressive primary malignant brain tumor in adults, characterized by limited treatment options and a poor prognosis. Previous drug repurposing efforts have yielded only marginal survival benefits, particularly those involving inhibitors targeting receptor tyrosine kinase and cyclin-dependent kinase-retinoblastoma pathways. This limited efficacy is likely due to several critical challenges, including the tumor’s molecular heterogeneity, the dynamic evolution of its genetic profile, and the restrictive nature of the blood-brain barrier that impedes effective drug delivery. Emerging diagnostic tools, such as circulating tumor DNA and extracellular vesicles, offer promising non-invasive methods for real-time tumor monitoring, potentially enabling the application of targeted therapies to more selected patient populations. Moreover, innovative drug delivery strategies, including focused ultrasound, implantable drug-delivery systems, and engineered nanoparticles, hold potential for enhancing the bioavailability and therapeutic efficacy of treatments.